Study on influence of external factors on the electrical excitability of PC12 quasi-neuronal networks through Voltage Threshold Measurement Method. - Xiao-Ying Lü; Chen Meng; Shuai An; Yong-Fang Zhao; Zhi-Gong Wang (PLoS ONE, 2022)
The aim of this paper was to investigate the influence of four different external factors (acetylcholine, ethanol, temperature and lidocaine hydrochloride) on PC12 quasi-neuronal networks by multielectrode-array-based Voltage Threshold Measurement Method (VTMM). At first, VTMM was employed to measure the lowest amplitude of the voltage stimulating pulses that could just trigger the action potential from PC12 quasi-neuronal networks under normal conditions, and the amplitude was defined as the normal voltage threshold (VTh). Then the changes of the VTh of PC12 quasi-neuronal networks treated by the four external factors were tested respectively. The results showed the normal VTh of PC12 quasi-neuronal networks was 36 mV. The VTh has negative correlation with the concentration of acetylcholine and has positive correlation with the concentration of ethanol. The curves of the correlation of the VTh with temperature and the concentration of lidocaine hydrochloride were U-shaped and Λ-shaped respectively. Comparing with our earlier studies on hippocampal neuronal networks and hippocampal slices, PC12 quasi-neuronal networks not only had the same typical voltage threshold characteristic, but also had similar changes on electrical excitability when treated by the four external factors mentioned above. Therefore, the rapid-formed PC12 quasi-neuronal networks could replace neuronal networks in proper conditions, and VTMM could be used to analyze the influence of external factors on the electrical excitability of PC12 quasi-neuronal networks.